Analisis Strategi Pemasaran Digital dalam Meningkatkan Loyalitas Konsumen Tokopedia: Perspektif Konsumen B2C di Sukabumi - Febrianty, Livia; Nurhasanah, Riska; Sulistiani, Hanum; Sazwan, Rifdi (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2025)
This study aims to analyze the digital marketing strategies implemented by Tokopedia in increasing consumer loyalty, particularly from the B2C consumer perspective in Sukabumi. Using a qualitative approach, the researchers conducted in-depth interviews with 10 Tokopedia users in Sukabumi who frequently made purchases through the platform. Data were collected using semi-structured interviews and documentation, then analyzed with a Miles and Huberman interactive model. The findings reveal that Tokopedia’s digital marketing strategies—such as personalized promotions, social media engagement, user-friendly interface, and reward systems—have significantly influenced consumer loyalty. Respondents indicated satisfaction with the ease of access, perceived value, and emotional connection to the brand. The study concludes that effective digital marketing strategies play a crucial role in shaping positive consumer experiences and fostering long-term loyalty.